2016
DOI: 10.1007/s11356-016-8185-9
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of high concentrations of mixed polycyclic aromatic hydrocarbons by indigenous bacteria from a river sediment: a microcosm study and bacterial community analysis

Abstract: This study assessed the biodegradation of mixtures of polycyclic aromatic hydrocarbons (PAHs) by indigenous bacteria in river sediment. Microcosms were constructed from sediment from the Chao Phraya River (the main river in Thailand) by supplementation with high concentrations of fluorene, phenanthrene, pyrene (300 mg kg of each PAH), and acenaphthene (600 mg kg). Fluorene and phenanthrene were completely degraded, whereas 50% of the pyrene and acenaphthene were removed at the end of the incubation period (70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…The diversification also included the enrichment of taxa belonging to genera with biodegradation potentials in the more polluted city of Baoding. While some of these genera were detected as rare members of the skin microbiota in this study and in previous reports [39][40][41], their ability to degrade PAHs [21,42] warrants further attention.…”
Section: Discussionsupporting
confidence: 52%
“…The diversification also included the enrichment of taxa belonging to genera with biodegradation potentials in the more polluted city of Baoding. While some of these genera were detected as rare members of the skin microbiota in this study and in previous reports [39][40][41], their ability to degrade PAHs [21,42] warrants further attention.…”
Section: Discussionsupporting
confidence: 52%
“…Some specific changes were observed that could be attributed to the presence of PAHs: the Actinobacteria , which were almost undetectable in the initial biofilm sample, increased up to 18% in the HMN and 2MN cultures and to almost 30% of the community in the NAP enrichment. Although an increase in the abundance of Actinobacteria has been related to the degradation of PAHs in aerobic conditions (Muangchinda et al ., ; Zhu et al ., ), there is no evidence of the contribution of this phylum to anaerobic degradation. Interestingly, an increase in the Acidobacteria candidate class iii1‐8 (order DS‐18) from undetectable levels in the initial biofilm sample to more than 9% of the community in the 2MN enrichment was also observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Co‐metabolic pathways and cross‐feeding among microorganisms are common phenomena in activated sludge. It has been reported that numerous bacterial genera and species are responsible for PAH degradation . In this study, the presence of some bacterial species bioaugmented our activated sludge.…”
Section: Resultsmentioning
confidence: 82%
“…Aromatic hydrocarbons are described as teratogenic, mutagenic, carcinogenic and potent immune suppressants due to their toxicity . Priority has been given to remove 16 PAHs from environmental systems by the US Environmental Protection Agency (EPA) …”
Section: Introductionmentioning
confidence: 99%